Pelaksanaan Praktikum Mata Kuliah Fisika Dasar I pada Program Studi Pendidikan Fisika FKIP UNSAM Semester Ganjil Tahun Akademik 2017/2018 - Teuku Hasan Basri; Bachtiar Akob (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2018)
Based on the Physics Education Study Program curriculum at the FKIP Samudra University, 1st Basic Physics course in the first semester of the lecture, where the course is 4 credits. The learning process, 3 credits of face-to-face process in the classroom, 1 credits carry out lab work in the laboratory. Problem formulation,